2017
DOI: 10.1590/s2175-97902017000115012
|View full text |Cite
|
Sign up to set email alerts
|

Solid lipid nanoparticles of irbesartan: preparation, characterization, optimization and pharmacokinetic studies

Abstract: Irbesartan is an antihypertensive with limited bioavailability and solid lipid nanoparticles (SLN) is one of the approaches to improve bioavailability. Solid lipid nanoparticles were prepared using glyceryl monostearate by solvent emulsification method followed by probe sonication. Irbesartan loaded SLNs were characterized and optimized by parameters like particle size, zeta potential, surface morphology entrapment efficiency and in vitro release. The optimized formulation was then further evaluated for the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 13 publications
(13 reference statements)
0
25
0
Order By: Relevance
“…Samples after appropriate dilutions in Milli Q water were taken for analysis. 16 Particle size analysis for the formulations was carried out following proper dilutions in Milli Q water at 25.1°C with equilibration time 70 s in triplicate.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…Samples after appropriate dilutions in Milli Q water were taken for analysis. 16 Particle size analysis for the formulations was carried out following proper dilutions in Milli Q water at 25.1°C with equilibration time 70 s in triplicate.…”
Section: Particle Size Analysismentioning
confidence: 99%
“…Also, it was observed that increase in drug payload resulted in sustained drug release pattern ( Figure 10) [19]. Sustained release pattern could possibly delay drug clearance, resulting in higher CFX blood level [48]. Drug release data was fitted well in to different kinetic-models which revealed that release of drug followed zero order kinetics (Table 3).…”
Section: Discussionmentioning
confidence: 94%
“…These results are in full agreement with (Soma et al, 2013), who studied the effect of increasing GMS on Irbesartan loaded SLNs. They proved that increasing concentration of GMS increased EE% [20].…”
Section: The Effect Of Lipid Concentration On Ee %mentioning
confidence: 96%
“…Infrared spectra of physical mixtures of pure TFH with each one of the used excipients, namely GMS, Tween 80 and Cremophor40, as well as those of the selected optimum formulae, were investigated using KBr discs. The IR spectra were obtained in the spectral region 4000-400 cm -1 [20].…”
Section: Infrared (Ir) Spectroscopymentioning
confidence: 99%